L’esprit de corps. Sur les ressorts imaginaires et affectifs du politique - Céline Hervet; Jacques-Louis Lantoine (Astérion)
This issue examines some of the philosophical problems around the concept of esprit de corps from three angles: the ambivalence of a concept that appears elusive, phantasmatic, even magical, yet which produces powerful effects of identification and political unification; the re-contextualisation and critique of the organicist metaphor of the ‘body politic’, where the very import of the democratic regime and society is tested, and finally, a revisitation of the Classical Age, in which the affective and imaginative triggers of social ties are brought to light, whether in terms of the relationships of subordination or solidarity that bind members of the same group together and ensure the cohesion of the social and political order.